Exercise as add-on therapy for smoking cessation in people with mental illness - Stefanie Schöttl; Prisca Kopp-Wilfling; Anika Frühauf; Carina Bichler; Martin Niedermeier; Monika Edlinger; Bernhard Holzner; Martin Kopp (Bern Open Publishing, 2024)
Introduction & Purpose The prevalence of smoking among people with mental illness is two to four times higher than in the general population. Unsuccessful quit attempts, often due to low confidence in their ability to quit, suggest that smokers with mental illness may benefit from additional smoking cessation strategies (Mann-Wrobel et al., 2011). Exercise as an adjunct treatment for smoking cessation in healthy individuals is increasingly recommended in the literature (Ussher et al., 2019), but there is limited data for people with mental illness. Therefore, the aim of this study is to evaluate the effectiveness of an exercise program as an add-on therapy for smoking cessation in people with mental illness. Methods 66 smokers with a diagnosed mental illness or mood disorders were included in a randomized controlled trial and received a standardized group smoking cessation program. Out of these 66 smokers, 38 individuals additionally participated in an exercise group (Nordic walking) and 28 in a control group (social contact group discussing health issues). Outcome variables were assessed by questionnaires at baseline (data available for 59 participants: 32 exercise group, 27 control group), during (after 3 weeks), and at the end of the program (5 weeks). Results The study had a dropout rate of 32%. At the end of the program, the abstinence rate was 19% in the exercise group and 30% in the control group (intention-to-treat analysis). There were no significant time-by-group interaction effects for any outcome variables. Significant group differences were found after 3 weeks for internal stimuli of self-efficacy (smokers' confidence to resist smoking in certain situations; p = 0.026, ƞ² = 0.121) and after 5 weeks for frequency (p = 0.003, ƞ² = 0.210) and intensity (p = 0.007, ƞ² = 0.174) of cigarette craving. The control group showed higher self-efficacy and lower frequency and intensity of cigarette craving compared to the exercise group. Main effects over time were observed in both groups with improvement in several outcome variables (e.g., self-efficacy, positive affect, frequency, and intensity of cigarette craving). Discussion Group differences may be explained by pre-existing differences in cigarette dependence, motivation to quit, and BMI at baseline. It is known from the literature that higher cigarette dependence can lead to less successful quitting and higher relapse rates (Gierisch et al., 2012). Participants also had difficulty integrating program content into their daily lives and had low attendance rates. According to Zhou et al. (2023), a higher adherence rate would lead to a higher quit rate. Since the study was conducted in groups, the influence of group dynamics on motivation to quit smoking needs to be considered. Conclusion An additional effect of exercise as an adjunctive therapy in smoking cessation could not be confirmed, since the control group showed better outcome scores. Due to the high dropout rate, further studies with larger samples are needed. Improving access to smoking cessation programs, developing additional strategies, integrating evidence-based treatment into existing settings, and training health care professionals to engage people with mental illness in smoking cessation remain important areas for improvement (Falcaro et al., 2021). References Falcaro, M., Osborn, D., Hayes, J., Coyle, G., Couperthwaite, L., Weich, S., & Walters, K. R. (2021). Time trends in access to smoking cessation support for people with depression or severe mental illness: A cohort study in English primary care. BMJ Open, 11(12), Article e048341. https://doi.org/10.1136/bmjopen-2020-048341 Gierisch, J. M., Bastian, L. A., Calhoun, P. S., McDuffie, J. R., & Williams, J. W. (2012). Smoking cessation interventions for patients with depression: A systematic review and meta-analysis. Journal of General Internal Medicine, 27(3), 351-360. https://doi.org/10.1007/s11606-011-1915-2 Mann-Wrobel, M. C., Bennett, M. E., Weiner, E. E., Buchanan, R. W., & Ball, M. P. (2011). Smoking history and motivation to quit in smokers with schizophrenia in a smoking cessation program. Schizophrenia Research, 126(1-3), 277-283. https://doi.org/10.1016/j.schres.2010.10.030 Ussher, M. H., Faulkner, G. E. J., Angus, K., Hartmann-Boyce, J., & Taylor, A. H. (2019). Exercise interventions for smoking cessation. The Cochrane Database of Systematic Reviews, 2019(10), Article CD002295. https://doi.org/10.1002/14651858.CD002295.pub6 Zhou, Y., Feng, W., Guo, Y., & Wu, J. (2023). Effect of exercise intervention on smoking cessation: A meta-analysis. Frontiers in Physiology, 14, Article 1221898. https://doi.org/10.3389/fphys.2023.1221898